Serving the poor: captive market CSR and repurchase intention. Issue 3 (18th May 2015) - Jose, Saju; Khare, Nilesh; Buchanan, F. Robert
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to examine whether corporate social responsibility (CSR) activities of the firm affect poor captive consumers' repurchase intentions, and whether or not CSR activities may moderate established relationships that drive repurchase intentions. Design/methodology/approach – A survey was administered to 201 poor microfinance borrowers at the bottom of the pyramid in India in a cross-sectional field study format. Multivariate regression is used to examine relationships between CSR and repurchase intention. Findings – All else being the same, CSR activities aimed at the borrowers' communities affects repurchase intentions positively even among poor captive borrowers. Further, positive perceptions of CSR to some extent mitigate the negative impact of the dissatisfaction on repurchase intentions. Unmarried borrowers, mostly female, were more moved by CSR impressions compared to their married counterparts. Research limitations/implications – Future research could identify other aspects of demographic differences in borrowers, and capture more about attitudes toward CSR and motivations for borrowing. Longitudinal study can establish causality that cannot be inferred from this cross-sectional field study. More diverse locations and organizations would offer wider generalizability. It will be interesting to examine if poor and captive customers would care about CSR activities even when such activities are targeted at recipients unrelated to them or their communities. Originality/value – The dynamics of CSR in poor captive consumer communities are somewhat novel. Microfinance context makes it even more so as the borrower is both a client and a recipient of CSR simultaneously. Results suggest that like well-off consumers, poor and captive customers also care about dissatisfaction and CSR.